Leisure Satisfaction: A Phenomenological Study on Baristas in a 24-Hour Coffee Shop - Wicaksono, Taufiq Nur (LifeSciFi, 2025)
Coffee shops that operate 24 hours implement shift work systems, particularly night shifts, which often cause physical and psychological fatigue among baristas and limit their ability to use leisure time optimally. This condition may reduce leisure satisfaction and negatively affect workers’ quality of life. This study aims to explore leisure satisfaction among baristas working in 24-hour coffee shops. A qualitative approach with a phenomenological method was employed to understand baristas’ subjective experiences related to leisure time. The participants consisted of two baristas working at a 24-hour coffee shop in Yogyakarta, selected using purposive sampling. Data were collected through in-depth interviews and analyzed using phenomenological stages, including bracketing, open coding, axial coding, and theme development. The findings indicate that baristas tend to experience low leisure satisfaction, influenced by work pressure, limited ability to manage leisure activities, and low social involvement. These conditions lead to work stress, continuous fatigue, and limited fulfillment of leisure satisfaction dimensions, including psychological, relaxation, physical, social, educational, and aesthetic aspects. The study concludes that the 24-hour work system contributes to low leisure satisfaction among baristas, highlighting the need for more flexible work arrangements and psychological well-being support to improve their quality of life and work performance.